CLINICAL BASIS OF DIPYRIDAMOL USE IN OBSTETRIC PRACTICE - S. V. Akinshina; V. O. Bitsadze; A. D. Makatsariya (IRBIS LLC, 2017)
The currently accepted role of hemostatic disorders (antiphospholipid syndrome, genetic thrombophilia) in the pathogenesis of frequent obstetric complications (preeclampsia, premature placental abruption, feto-placental insufficiency, recurrent miscarriage) revolutionized the prevention and treatment of these pregnancy-associated abnormalities. An increasing number of direct and indirect anticoagulants have been introduced into clinical practice. The present review addresses the mechanisms of action of dipyridamole, an antiaggregant medication commonly used in obstetrics. In addition to its antiplatelet activity, dipyridamole is also known for other pharmacological effects, including the antioxidant and endothelioprotective activities.